2021
DOI: 10.1111/phn.12853
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of learning outcomes from two poverty simulation experiences

Abstract: Objectives: Five nationally representative U.S. federal data sources consistently showed the link between poverty and poor health outcomes. To determine the modality effective in teaching students about poverty and health, this study compared the attitudes toward poverty of students participating in the Community Action Poverty Simulation (CAPS) and the poverty table-top simulation (Dwell™). Methods:In this quasi-experimental study, undergraduate and graduate nursing students and physical therapy students part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Each of the 9 studies that met inclusion criteria for this review used simulated participants (SPs). [17][18][19][20][21][22][23][24][25] Four of the 9 studies incorporated the International Nursing Association for Clinical Simulation and Learning (INACSL) 26 Healthcare Simulation Standards of Best Practice (HSSOBP). [17][18][19][20] The included studies reflected…”
Section: Resultsmentioning
confidence: 99%
“…Each of the 9 studies that met inclusion criteria for this review used simulated participants (SPs). [17][18][19][20][21][22][23][24][25] Four of the 9 studies incorporated the International Nursing Association for Clinical Simulation and Learning (INACSL) 26 Healthcare Simulation Standards of Best Practice (HSSOBP). [17][18][19][20] The included studies reflected…”
Section: Resultsmentioning
confidence: 99%
“…This finding might be justified because limited systematization of poverty teaching assessment occurs in the training of nursing students, and when this content is offered, it occurs in an unsystematic and sporadic way in classes (Blair, 2010), not as part of the curricular component of undergraduate courses (Dos Santos et al, 2017;Watts et al, 2021). Knowledge of the effective ways to teach students about the intersection of poverty and health is still scarce (Reutter et al, 2004;Sanko et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The Poverty Simulation was selected as an experiential method to teach students to achieve these goals. Previous research has demonstrated that the Poverty Simulation method may be an appropriate way to educate students on the topic of poverty (Cotton, 1992;Hurley et al, 2021;Nickols & Nielsen, 2011;Sanko et al, 2021;Segal, 2007;van Berkhout & Malouff, 2015). The purpose of this study was to expand on the current literature associated with attitudes toward poverty to see how participation in the Poverty Simulation impacted students from different disciplines.…”
Section: Purposementioning
confidence: 99%